Male/female roles opposing viewpoints - Petrikin, Jonathan S. (San Diego, California Greenhaven Press, 1995)
Various authors debate how sex roles were established and how men and women respond to changes in sex roles. Includes critical thinking skills activities.
Evolution explains traditional gender roles / Anthony Layng -- Evolution does not explain traditional gender roles / Carol Tavris -- Biology determines gender roles / James C. Dobson -- Biology does not determine gender roles / Ruth Hubbard -- Brain structure explains male/female differences / Yves Christen -- Brain structure does not explain male/female differences / Le Anne Schreiber -- Economics determines gender roles / Francine D. Blau & Marianne A. Ferber -- Culture determines gender roles / Linda L. Lindsey -- A glass celing limits women's roles at work / Business and Professional Women's Foundation --The glass ceiling is not what limits women at work / George Gilder -- Gender issues are helping women win in politics / Mary Beth Rogers -- Gender issues are not helping women win in politics / Marian Lief Palley -- Women's opportunities in the military are improving / Amy Pagnozzi & Bruce W. Nelan -- Women's opportunities in the military are dangerous / Elaine Donnelly & Phyllis Schlafly -- Women can have it all / Rosalind C. Barnett & Caryl Rivers -- Women cannot have it all / Nancy Pearcey -- Men's lives are changing for the better / Sam Julty -- Men's lives are changing for the worse / Warren Farrell -- Men need to become more manly / Robert Bly -- Men do not need to become more manly / Fred Pelka -- Men need to form close male friendships / Terry A. Kupers & Larry Letich -- Men are already forming close male friendships / Alan Buczynski, Mike Yorkey & Peb Jackson -- Men are becoming better fathers / Kathleen Gerson -- Men are not becoming better fathers / Wade C. Mackey & Ursula White -- Working parents help their children / Faye J. Crosby -- Working parents harm their children / Sylvia Ann Hewlett -- Day care harms children / J. Craig Peery -- Day care does not harm children / Susan Faludi & Rosalind C. Barnett -- Families need government-subsidized child care / Sheila B. Kamerman -- Families do not need government-subsidized child care / Allan Carlson -- Marriage is becoming more popular / Diane Medved -- Marriage is not becoming more popular / Norval D. Glenn -- Men and women should share domestic responsibilities / Arlie Hochschild with Anne Machung -- Men and women should not share domestic responsibilities / Steven Goldberg -- Sexual attraction in the workplace is often counterproductive / Lisa A. Mainiero -- A new sexual dynamic in the workplace can be beneficial / David R. Eyler & Andrea Baridon.
Includes bibliographical references (pages 303-304) and index.
Keywords: Sex role; Sex role -- United States